Redefining implicit and explicit memory: The functional neuroanatomy of priming, remembering, and control of retrieval - Schott, Björn H. (National Academy of Sciences, 2005)
We used event-related functional MRI to study awareness of prior episodes during memory retrieval and its relationship to the intention to retrieve memories. Participants completed cues with words from a prior list (intentional test) or with the first words that came to mind (incidental test). During both tests, explicit memory was separated from priming in the absence of explicit memory. Priming was associated with hemodynamic decreases in left fusiform gyrus and bilateral frontal and occipital brain regions; explicit memory was associated with bilateral parietal and temporal and left frontal increases. Retrieval intention did not change these patterns but was associated with activity in right prefrontal cortex. Our results provide firm evidence that implicit and explicit memory have distinct functional neuroanatomies, and that strategic control of retrieval engages brain structures distinct from those involved in both implicit and explicit memory. They have critical implications for theories of memory and consciousness, which often equate consciousness with control.